Kilka uwag na temat normatywności w teorii polityki: perspektywa utopii politycznej - Olbromski, Cezary J. (Wydział Nauk Politycznych i Dziennikarstwa UAM w Poznaniu, 2011)
In the opinion of the author, the current dimension of politicization depends on how efficient political activity is. It constitutes the realm of the increasingly professional activity intended to match the current, increasingly limited politicization. At the same time, the assessment of what we are presented with in an everyday agenda both restricts the discourse to the quantitative evaluation of politicians’ activities and limits the level of political participation of citizens. Our turbulent civilization forces us to plan more and more precisely, but at the same time it reduces the temporal perspective of political activity. The author attempts to answer the question of whether the state is becoming a ‘factory’ managed by the elites that are no longer politicized. In his opinion, the answer to this question should be: no, it isn’t.